Longitudinal recovery of local neuronal activity and consciousness level in acquired brain injury. Issue 7 (19th April 2017) - Zou, Qihong; Wu, Xuehai; Hu, Jin; Tang, Weijun; Mao, Ying; Zhu, Jianhong; Lu, Lu; Zhang, Yao; Gao, Jia‐Hong
Abstract: Decreased brain activity in the default mode network, particularly in the precuneus (PCU), has been consistently shown in acquired brain injury (ABI) patients. However, it is unclear whether resting‐state brain activity recovers longitudinally in ABI patients and whether functional activity restoration is associated with improvements in consciousness level. Here, resting‐state fMRI data were acquired from 23 ABI patients and 30 age‐ and gender‐matched controls with two longitudinal observations for each participant. The fMRI data were analyzed using amplitude of low‐frequency fluctuation (ALFF) to measure the fluctuation strength of local spontaneous activity, and seed‐based functional connectivity was used to measure functional relationship with the seed region in the whole brain. The level of consciousness was assessed using the Glasgow Coma Scale (GCS) and Coma Recovery Scale‐Revised (CRS‐R) on both scanning days of the patients. Interaction effect between the two groups and two scans in ALFF was observed in the PCU, which was driven by restored ALFF in the ABI, while a stable ALFF in the control group. Moreover, restoration of ALFF in the PCU correlated with improvements in both the CRS‐R and GCS. Specifically, recovery of ALFF in the PCU primarily reflected the signals of the slow‐4 frequency band (0.027–0.073 Hz). Based on the functional connectivity maps of the PCU, we observed a nonsignificant interaction effect or correlation with consciousness level. These findings suggest local activity in the PCU but possibly not its functional connectivity, is related to the longitudinal changes in behavioral responsiveness in ABI. Hum Brain Mapp 38:3579–3591, 2017 . ©2017 Wiley Periodicals, Inc.